The Role of Supervisory and Leadership Type in Budgeting Commitment on Hospitals’ Financial Performance in East Java Province, Indonesia (International Journal of Management and Sustainability, 2016)
Analysis of an organization’s financial performance reveals whether an organization’s financial condition is performing better or worse. This reflects its performance and achievement in that time period. In order to achieve good financial performance, the organization’s staffs need to be committed to work according to the organization’s plans and its budgetary commitment. Leadership type is crucial in determining the organization’s success because it affects and enhances the staff’s commitment to participate in creating and implementing the organization’s budget. Supervision control is needed to ensure that budgetary commitment is on target and does not deviate from its predetermined commitment. This study to analyzed the role of supervisory role and leadership type on budgetary commitment and financial performance across 15 hospitals in East Java, Indonesia. 10 participants were surveyed from each hospital with questionnaires about supervisory role, leadership type, budgetary commitment, and financial performance. We also obtained secondary data in the form of financial statements from each hospital and later correlated this data with our questionnaire using a path analysis computer software Smart Partial Least Square. The results showed that a hospital’s managerial supervision (estimated path coefficient = 0.222, p=0.001) and its leadership type(estimated path coefficient= 0.572, p=0.000) positively influenced the hospital’s budgetary commitment. Leadership type(estimated path coefficient = 0.294, p =0.020) and budgeting commitment(estimated path coefficient= 0.243, p=0.030) directly influenced a hospital’s financial performance. While managerial supervision has no direct effect on a hospital’s financial performance (estimated path coefficient = 0.130, p=0.125), it exerts its effects on financial performance indirectly through its effect on budgetary commitment.